(untitled) (REVISTA NODO, 2026)
Through exhaustive research in the archives of the Mexican Art Gallery, Eréndira Derbez takes us to discover how Inés Amor made her way in a male-dominated world and defied stereotypes to become one of the most influential figures in Mexican art.